PENGARUH STRUKTUR MODAL DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING ( STUDI EMPIRIS PADA PERUSAHAAN REAL ESTATE & PROPERTY YANG TERDAFTAR DI BEI PERIODE 2009 - 2013 ) - Adi Chandra; Kamaliah Kamaliah; Restu Agusti (Jurnal Ekonomi, 2016)
This study was conducted to test (1) The effect of capital structure onprofitability,(2) The effect of size of firm on profitability,(3) The effect ofprofitability on firm value,(4) Effect of meditation profitability of the relationshipbetween capital structure and firm value, and (5) Effect of meditation profitabilityof the relationship between size of firm and firm value. Object under study is areal estate & property companies listed on Indonesian Stock Exchange during theperiod 2009-2013 with a total sample some 23 companies. This study usessecondary data obtained from Indonesian Stock Exchange. Testing is done byusing path analysis by using SPSS version 21. Prior to testing, conducted priortest data normality adn linearity test.The result showed that (1) Capital structure influence on profitability,(2) size offirm influence on profitability,(3) Profitability affected the firm value, (4)Profitability mediated the effect of capital structure on firm value ,and (5).Profitability does not mediated the effect of size of firm on firm value.